2019
DOI: 10.20870/oeno-one.2019.53.4.2470
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to organic and biodynamic viticultural practices: impact on soil, grapevine development and grape quality

Abstract: Aim: The effects of integrated, organic and biodynamic management on soil quality and the growth and morphological development of Riesling grapevines were assessed during the first 4 years of a long-term field trial in Geisenheim, Germany. The overall aim was to understand the effects of these different viticultural practices on soil quality and plant morphology as the basis for product quality.Methods and results: As indicators of soil quality, earthworm abundance and the activity of selected enzymes were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…It is noteworthy that, in the case of Spain, only biodynamic samples show clustering coefficient (+) scores different (higher) from those expected by random, highlighting the outstanding structure of fungal communities under this type of management. Ultimately, biodynamic management has been reported to lead to higher-quality grapes in vineyards than conventional management, with organic practices showing an intermediate effect, based on soil fertility, nutrient availability, enzyme activity, and earthworm abundance ( 26 ). Taking our results together, we have observed that communities with lower modularity (+) had higher completeness of modules that were associated with wider temperature ranges ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that, in the case of Spain, only biodynamic samples show clustering coefficient (+) scores different (higher) from those expected by random, highlighting the outstanding structure of fungal communities under this type of management. Ultimately, biodynamic management has been reported to lead to higher-quality grapes in vineyards than conventional management, with organic practices showing an intermediate effect, based on soil fertility, nutrient availability, enzyme activity, and earthworm abundance ( 26 ). Taking our results together, we have observed that communities with lower modularity (+) had higher completeness of modules that were associated with wider temperature ranges ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that land use and crop management have a strong effect on fungal soil ecosystem functioning ( 1 , 24 , 25 ). When contextualizing community-level properties into management, we will consider that agroecosystems in general, and vineyards in particular, can be managed under three different intensification levels, according to how cultural, biological, and mechanical practices foster the cycling of resources, promote ecological balance, or conserve biodiversity ( 26 ): (i) “conventional” management, which allows a wide variety of chemical fertilizers or pesticides; (ii) “organic” management, subjected to strict limits on the use of mineral nitrogen fertilizers and synthetic phytosanitary products; and (iii) “biodynamic” management, as an extreme scenario that rejects the use of mineral nitrogen fertilizers and synthetic pesticides but promotes the use of compost-based fertilization and cover crops, and the use of specific preparations—based on fermented plant materials—to enhance soil fertility and microbial diversity. Since geography, climate, and agriculture management are likely to affect the composition of fungal communities in vineyard soils ( 27 ), here we aimed to delve into the functional implications of these changes, understanding whether the structure of local fungal networks can give information about the dominant ecological processes in fungal communities.…”
Section: Introductionmentioning
confidence: 99%
“…Lower yields than the regional reference, are also reported in organic farming in the scientific literature (Seufert et al, 2012;Meissner et al, 2019). As such, the agronomic diagnosis for the PACA case study aimed to explain the yield variability when grapevines are grown according to organic standards.…”
Section: Regional Agronomic Diagnosis In Organic Farming (Paca Case Study)mentioning
confidence: 97%
“…Organic viticulture is rapidly spreading worldwide because it offers multiple advantages over conventional cultivation (Probst, B. et al 2008;Provost, C. and Pedneault, K. 2016), producing high quality grapes and wines with lower inputs, conserving biodiversity and keeping pests and diseases at low levels. In organic viticulture only organic fertilizers and non-synthetic pesticides are allowed and soil disturbance is reduced by minimum tillage and grassing (Meissner, G. et al 2019). Biodynamic viticulture, where specific preparates are applied to enhance bacterial action, is also popular in many countries (Meissner, G. et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In organic viticulture only organic fertilizers and non-synthetic pesticides are allowed and soil disturbance is reduced by minimum tillage and grassing (Meissner, G. et al 2019). Biodynamic viticulture, where specific preparates are applied to enhance bacterial action, is also popular in many countries (Meissner, G. et al 2019). In southern France conversion to organic viticulture was found to significantly increase bulk density, total organic carbon content (TOC) and cation exchange capacity (CEC) of soils (Coll, P. et al 2011).…”
Section: Introductionmentioning
confidence: 99%